2003
DOI: 10.1034/j.1600-0773.2003.920408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Environmental Oestrogens Bisphenol A, Tetrachlorobisphenol A, Tetrabromobisphenol A, 4‐Hydroxybiphenyl and 4,4′‐Dihydroxybiphenyl on Oestrogen Receptor Binding, Cell Proliferation and Regulation of Oestrogen Sensitive Proteins in the Human Breast Cancer Cell Line MCF‐7

Abstract: Bisphenol A is extensively used in the manufacturing of epoxy resins and polycarbonate plastics, whereas several brominated and chlorinated analogues are used as flame retardants and intermediates in the plastic industry. Due to the structural relationship between these chemicals and the high production volumes, we wanted to characterize and compare their potential oestrogen-like potency using several end-points in MCF-7 cells: induction of pS2 protein and progesterone receptor, reduction of oestrogen receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 73 publications
(80 reference statements)
6
50
0
Order By: Relevance
“…The low binding affinity of BPA to classical ERs explains its inability to exert a strong mitogenic activity in MCF7 cells. One study found increased cell proliferation in response to BPA only at 60 000 times higher concentrations than E 2 (Olsen et al 2003). Another group confirmed that BPA at a relatively high dose (1 mM) showed a modest stimulation of proliferation of MCF7 cells cultured in estrogen-depleted medium, while E 2 was effective at subnanomolar concentrations (Hess-Wilson et al 2006).…”
Section: Bpa Breast Cancer and Chemoresistancementioning
confidence: 52%
“…The low binding affinity of BPA to classical ERs explains its inability to exert a strong mitogenic activity in MCF7 cells. One study found increased cell proliferation in response to BPA only at 60 000 times higher concentrations than E 2 (Olsen et al 2003). Another group confirmed that BPA at a relatively high dose (1 mM) showed a modest stimulation of proliferation of MCF7 cells cultured in estrogen-depleted medium, while E 2 was effective at subnanomolar concentrations (Hess-Wilson et al 2006).…”
Section: Bpa Breast Cancer and Chemoresistancementioning
confidence: 52%
“…Cultured MCF-7 breast cancer cells show a weak estrogenic response to TBBPA (Körner et al 1998;Olsen et al 2003), and TBBPA inhibits in vitro estradiol sulfonation (Hamers et al 2004), indicating potential for both direct and indirect estrogenic activity in vivo. Increased uterus weights in ovariectomized mice exposed to TBBPA for 3 days (20 mg/kg/day, intraperitoneal) confirm estrogenicity in vivo (Kitamura et al 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro investigations of the molecular mechanism of xenoestrogen effects have been focused on the proliferation test of ERa-expressing MCF-7 cells, binding assays with ERs (a and b), reporter gene assays using ERE (Soto et al 1995, Kuiper et al 1997, Andersen et al 1999, Legler et al 1999, Balaguer et al 2001, Diel et al 2002, Olsen et al 2003, or a few estrogen target gene promoters (Hall & Korach 2002). Recently, a DNA microarray was also developed to evaluate the estrogenic activity of industrial chemicals (Terasaka et al 2004).…”
Section: Introductionmentioning
confidence: 99%